Firstly, since its a +x^3 type graph, its going to go up, down, and up again.
Now, first solve it = 0. x^3 + 2x^2 - 3x = 0, so x(x^2+2x-3) = 0, so x(x+3)(x-1) = 0. That means x = -3, 0 or 1 are the three roots.
Thus, we know it starts off very small, goes up to 0 when x=-3, keeps going up into the positives and down again to x=0, down into the negatives and up again to x=1, and finally up to infinity for x>1.
Thus the parts where it is positive are between -3 and 0, and > 1.
Or (-3,0) union (1,∞)
2006-12-01 09:32:41
·
answer #1
·
answered by stephen m 4
·
0⤊
0⤋
Solve first for x intercepts (zeros).
x(x² + 2x - 3) = 0
x(x + 3)(x - 1) = 0
zeros at -3, 0, 1
Since the x^3 coefficient is >0, the graph goes low left and high right, squiggle in the middle. So the polynomial > 0 when
x in (-3,0) and (1,â).
2006-12-01 17:36:14
·
answer #2
·
answered by Philo 7
·
0⤊
0⤋
First off, we factor the left hand side of the inequality.
x(x^2 + 2x - 30) > 0
Are you sure you typed this question correctly? I'm going to assume the middle term has no 2 in it, giving us
x(x^2 + x - 30) > 0
x(x+6)(x-5) > 0
At this point, you note that your critical points are when the left hand side is equal to 0. That is, x = 0, -6, and 5
You then make a number line, with 0, -6, and 5 being the separators.
-------------------------------------
-6||||||||||||||||||||||0||||||||||||||||||||||||||5
At this point, you test each of the intervals into the given polynomial to see if you get a positive or negative number. You can even test 1,000,000,000, and you'll find that you get a positive number testing that. From that point, it will alternate.
Thus, since it's positive from 5 to infinity, it'll be negative from 0 to 5, positive from -6 to 0, and negative from -infinity to -6.
Since you're only interested in where it's strictly positive, your intervals are:
(-6,0) union (5 to infinity)
2006-12-01 17:36:28
·
answer #3
·
answered by Puggy 7
·
0⤊
1⤋
factor x
x^3+2x^2-3x>0 ==> x(x^2+2x-3)>0
then solve for x,
x( x -1)(x + 3) > 0
so x( x -1)(x + 3) = 0 has solution when x =0, x = 1, and x = -3
draw a table
x = - infinite ***-4 *** -3 ***-1*** 0 ***0.5*** 1 ***2***positive inf.
x = '''''''''-'''''''''''''' -''''''''' -''''''''''' -''''''''' 0''''''' +''''''''' +''''' + '''''''' +
x-1 =''''''' -''''''''''''' -''''' - ''''''''' - '''''''''' -'''''''' -''''''''' 0''''''+'''''''''''+
x+3 =''''''-'''''''''''''' -'''''''''' 0'''''''+ '''''''''+'''''''''+'''''''''' +''''' +''''''''' +
f(x) =''''' - ''''''''''' -'''''''''''''0 ''''''+ ''''''''' 0 ''''''' - ''''''' 0'''''+'''''''''+
Note f(x) = x(x-1)(x+3)
so f(x) > 0 when -3 < x <0 or 1< x
2006-12-01 17:33:46
·
answer #4
·
answered by ___ 4
·
0⤊
0⤋